(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article deals with the psychological aspects of the phenomenon of existential conflict in the worldview content of a new type of personality. The essence of existential conflict in the story of Honore de Balzac «Gobsheck» is outlined, the psychological characteristics of the confrontation between man and society are explained, which causes alienation of the person from the world and from himself. The essence of artistic psychologism in literary works is determined. The author presents the results of empirical study of typical models of conflicting behavior of young schoolchildren. The problem of development of constructive worldview of schoolchildren in the educational system, and in particular in the study of literature, is emphasized. The problem of organizing the work of a teacher with students in foreign literature lessons is considered.